Evaluation of potential changes in liver and lung tissue of rats in an ischemia-reperfusion injury model (modified pringle maneuver) - Freitas, Silvio Henrique; Doria, Renata G. S.; Bueno, Rachel S.; Rocha, William B.; Filho, Jair R. E.; Moraes, Julieta R. E. [UNESP]; Vidane, Atanasio Serafin; Ambrosio, Carlos E. (Public Library Science, 2017)
In surgical procedures involving the liver, such as transplantation, resection, and trauma, a temporary occlusion of hepatic vessels may be required. This study was designed to analyze the lesions promoted by ischemia and reperfusion injury of the hepatic pedicle, in the liver and lung, using histopathological and immunohistochemical techniques. In total, 39 Wistar rats were divided into four groups: control group (C n = 3) and ischemia groups subjected to 10, 20, and 30 minutes of hepatic pedicle clamping (I10, n = 12; I20, n = 12; I30, n = 12). Each ischemia group was subdivided into four subgroups of reperfusion (R15, n = 3; R30, n = 3; R60, n = 3; R120, n = 3), after 15, 30, 60, and 120 minutes of reperfusion, respectively. Significant differences were observed in the liver parenchyma (P < 0.05) between the values of microvesicles and hydropic degeneration at different times of ischemia and reperfusion. However, the values of vascular congestion, necrosis, and pyknotic nuclei showed no significant differences (P > 0.05). In the lung parenchyma, a significant difference was observed (P < 0.05) between the values of alveolar septal wall thickening and inflammatory infiltration at different times of ischemia and reperfusion. However, there was no significant difference (P < 0.05) between the values of vascular congestion, bronchial epithelial degeneration, interstitial edema, and hemorrhage. The positive immunoreactivity of caspase-3 protein in the liver parenchyma (indication of ongoing apoptosis), showed no significant differences (P > 0.05) at different times of ischemia and reperfusion. In the pulmonary parenchyma, the immunoreactivity was not specific, and was not quantified. This study demonstrated that the longer the duration of ischemia and reperfusion, the greater are the morphological lesions found in the hepatic and pulmonary parenchyma.